Design, optimization, and antimicrobial assessment of Callicarpa longifolia-derived nanoparticles using quality by design (QbD) approach - Md. Shakeel Alam; Srivastava, Nidhi (Creative Pharma Assent, 2025)
Background: The purpose of this study is to focus on the design, optimization, and antimicrobial evaluation of ethanolic leaf extracts of Callicarpa longifolia-derived nanoparticles using the Quality by Design (QbD) technique. Methodology: Critical formulation parameters were optimized using a Box-Behnken Design. The optimized nanoparticles are characterized using Dynamic Light Scattering (DLS), Zeta Potential analysis, and Scanning Electron Microscopy (SEM), confirming their nanoscale size. Stability studies were conducted under various ICH recommendations. The antimicrobial activity of the isolated fraction extract and isolated fraction extract nanoparticles was assessed against Gram-positive (Staphylococcus aureus) and Gram-negative (Escherichia coli) bacteria using the agar well diffusion method. Results and Discussion: By BBD, the optimized herbal nanoparticles have a particle size of 281.00 nm and an entrapment efficiency 88%. After characterization, the results of the optimized nanoparticles' particle size (349.3 nm), zeta potentials (-23.7 mV), % EE (86.25%), and spherical shape are confirmed by SEM. The % cumulative drug release of optimized nanoparticles is 86.12±0.79. Kinetic release model regression values of the optimized nanoparticles' R² values in different model kinetic releases are zero order (0.929), first order (0.971), Higuchi kinetic release (0.994), Korsmeyer kinetic release (0.994), and Hixon Crowell (0.978). Results revealed that the nanoparticle formulation exhibited significant antimicrobial efficacy. Conclusion: All things considered, the study shows how the QbD methodology may be successfully applied to create a stable and efficient nanoparticle system made from an isolated extract of C. longifolia, which has encouraging potential as a substitute antibacterial agent.